Multiliteracies and family language policy in an urban Inuit community - Patrick, D. (Donna); Budach, G. (Gabriele); Muckpaloo, I. (Igah) (Language Policy, 2013)
This study investigates the intersection of family language policy with Indigenous multiliteracies and urban Indigeneity. It documents a grassroots Inuit literacy initiative in Ottawa, Canada and considers literacy practices among Inuit at a local Inuit educational centre, where maintaining connections between urban Inuit and their homeland linguistic and cultural practices is a central objective. Using data from a participatory, activity-oriented, ethnographic project at an Inuit family literacy centre, we argue that state-driven language policies have opened up spaces for Indigenous-defined language and literacy learning activities that can shape and be shaped by family language policies. This has permitted some urban groups in Canada to define their own literacy needs in order to develop effective family language policies. Drawing on two Inuit-centred literacy activities, we demonstrate how literacy practices are embedded in intergenerational sharing of Inuit experience, cultural memory, and stories and how these are associated spatially, culturally, and materially with objects and representations. We thus show how Inuit-centred literacy practices can be a driving force for family language policy, linking people to an urban Inuit educational community centre and to their urban and Arctic Inuit families and homelands.